Transformasi Bundaran Besar Kota Palangka Raya dari Ruang Simbolik menjadi Ruang Publik Aktif bagi Komunitas Olahraga: The Transformation of the Big Roundabout in Palangka Raya City from a Symbolic Space into an Active Public Space for the Sports Community - Arafat, Arafat; Fitriani, Fitriani (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
The Great Roundabout of Palangka Raya City is one of the city spaces with high symbolic value as a center of orientation and a landmark of regional pride. Along with urban dynamics and changes in people's lifestyles, this symbolic space has undergone a shift in function into an active public space. This study aims to analyze the transformation of the Great Roundabout of Palangka Raya City from a symbolic space into an active public space for sports communities, identify the factors driving the change, and examine its impact on the community's social life. The study used a descriptive qualitative approach with data collection techniques through field observations, interviews with space users and sports communities, and documentation. Data analysis was carried out interactively through the stages of data reduction, data presentation, and drawing conclusions. The results show that the Great Roundabout has undergone a significant transformation in function, marked by an increase in the intensity of space use for jogging, running, group exercise, and cycling activities carried out routinely by various community groups. This transformation is influenced by increasing public awareness of the importance of a healthy lifestyle, the limited alternative green open spaces in urban areas, and the strategic accessibility of the Great Roundabout. The existence of sports communities plays a significant role in enlivening public spaces, encouraging social participation, and strengthening interactions between residents. The findings of this study provide implications for the management of urban public spaces based on community participation.